Bury the lede - Dunn, Gaby (BOOM! Studios, a division of Boom Entertainment, Inc., 2019)
Cub reporter Madison Jackson is young, scrappy, and hungry to prove that she deserves her coveted college internship at the premiere newspaper in town. The Boston Lede, where she fetches coffee for the night crew and dreams of her own byline. So when her police scanner mentions a brutal murder tied to a prominent Boston family, Madison races to the crime scene, looking for the scoop of the century. What she finds instead is the woman who'll change her life forever: Dahlia Kennedy, celebrity socialite, now widow, covered in gore and the prime suspect in the murder of her husband and child. When Dahlia refuses to talk to anyone but Madison, they begin a dangerous game of cat and mouse that leads the young journalist down a twisted path--back cover.